Pengaruh Return on Asset, Return on Equity Terhadap Harga Saham pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia pada Tahun 2019–2021 - Laily, Syafaatul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to investigate the influence of Return on Assets (ROA) and Return on Equity (ROE) on share prices in manufacturing companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange during the 2019–2021 period. The sampling method used was purposive sampling with certain criteria. Ten companies were selected as samples from a population of 47 Food & Beverage Manufacturing companies after applying the purposive sampling method. Analysis was carried out through multiple regression and hypothesis testing using the partial t-test, simultaneous F test with a significance level of 5%, and coefficient of determination test. This research aims to provide a deeper understanding of the relationship between Return on Assets (ROA) and Return on Equity (ROE) with stock prices in the context of Food and Beverage manufacturing companies. The results of this research are expected to provide a significant contribution to academic and practical literature in the field of corporate finance. Therefore, this research has relevant implications for investors, company management, and interested parties in making investment decisions in the Food and Beverage sector.